Influence of the online learning environments and tools on the student achievement and opinions - Atici, Bünyamin; Polat, Oznur Cevik (My University, 2010)
The purpose of this study is to determine the influence of the instructional usage of the online tools on the student success and opinions in Science Education. This study, in which it tried to determine the influence of the instructional usages of the tools on the student achievement and opinions, is designed as an experimental study with the trial model. The working field of the study is composed of the eighth grade students of primary school. The sample of the study is composed of 45 primary school students having computer and internet connection. In this line, the experimental and control groups are formed from the students who are selected randomly among the students between the ranges of 300 - 350 for SBS examination grade range of the academic year of 2008-2009. Some of the findings which are obtained as a result of the study carried out qualitatively and quantitatively are as follows; it was seen that the participants took education in Test-2, that is to say, in blended learning environment between the successes of the Test-1, Test-2 and control groups. It was determined that only the students who took education in the online learning environment had more positive opinions for the online instructional tools. © 2010 Academic Journals.
Keywords: Achievement; Blog; Moodle; Online learning